In search of sustainable business models for cognitive radio evolution - V. Fomin, Vladislav; Medeišis, Artūras; Vitkutė-Adžgauskienė, Daiva (Technological and Economic Development of Economy, 2012)
In this paper we examine the emerging industry of Cognitive Radio/Software Defined Radio (CR/SDR), a sector which in some ways seconds the industry structure of the cellular mobile communications, while bearing distinctive characteristics. Any radio telecommunications infrastructure depends on scarce resources – radio frequency spectrum – that require policy decisions for allocation to specific countries and services. CR/SDR may constitute a new paradigm in radio communications as it may completely or partially eliminate the role of the regulator in minutiae of spectrum access authorization.In this paper, we review scarce literature on CR/SDR to analyze the relationships between political, technological and economic factors in order to identify drivers and barriers to the emergence of new techno-economic paradigm of CR/SDR. Our discussion of business opportunities for CR/SDR includes analysis of applicable spectrum access policies and identification of those of them, which would be most fertile for the development of future CR/SDR business.